STANDAR PENGUPAHAN DALAM EKONOMI ISLAM (Studi Kritis atas Pemikiran Hizbut Tahrir) - Syakur, Ahmad (IAIN Kediri, 2015)
The labour and wage problems is one of central issues in the contemporary industrial economy. Wagework is theÃ‚Â leading provider of tax-advantage consumer directed health, commuter and other employee benefi t. In order toÃ‚Â compromise between employee and employer interest, the government set a minimum regional wage. MinimumÃ‚Â wage policy in Indonesia is set based an a survey of decent living needs.Ã‚Â Hizbut Tahrir is one of Islamic movement that calls to return to the practise of Islam in the all of life sides. Then,Ã‚Â Hizbut Tahrir concerns to study of Islamic economy, especially the economy of Islamic state and public fi nance.Ã‚Â Hizbut Tahrir has different opinion with other moslem economic about standard wage rates.Ã‚Â Standard wage rates Ã¢â‚¬â€œ refers Hizbut Tahrir opinions- is only based the work utility of labor. The basic livingÃ‚Â needs cannot be the standard of wage. The wage rate is prerogative right of employee and employer, describedÃ‚Â a agreement based the utility of work. This opinion different with mainstream moslem economic. AccordingÃ‚Â to maintreams moslem economic, standard of wage not only based work utility of labor, but also based decentÃ‚Â living needs.Keyword: Standard, wage, living needs, Islamic economy